Intercostal Nerve Blocks Using Liposomal Bupivacaine. Issue 1 (11th March 2015) - Hofer, Ryan; Rosenberg, Casandra; Niesen, Adam; Amundson, Adam; Eldrige, Jason
Summary: A 51‐year‐old male was admitted to the intensive care unit following a cardiac arrest during which he received chest compressions and suffered rib fractures. The patient's condition subsequently improved and tracheal extubation was eventually planned. However, he was unable to tolerate spontaneous breathing trials due to pain from his rib fractures. Systemic analgesia provided either insufficient pain control or over‐sedation. Neuraxial techniques were contraindicated as he was receiving systemic anticoagulation and antiplatelet medications. Intercostal nerve blocks with liposomal bupivacaine were performed under ultrasound guidance without complications. Approximately six hours after the injections, the patients trachea was successfully extubated with no further need for respiratory support through to discharge. In appropriately selected patients, intercostal nerve blocks with liposomal bupivacaine can adequately treat pain from rib fractures and improve respiratory mechanics.